METODE BUDIDAYA JAMUR ASLI INDONESIA DAN MANFAATNYA: TINJAUAN SISTEMATIS - Vanessa Setiaanggara (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Mushrooms are a high-quality source of nutrition, tonic, medicinal, and nutritional food that is growing and consumed globally. Due to their excellent nutrients, mushrooms have always been valued for their vital role in protecting and treating health problems. It appears that there has been no review summarizing the medicinal benefits of mushrooms, even though it is crucial to provide an insight into the cultivation of Indonesian mushrooms and their medicinal benefits. This systematic review aims to summarize the cultivation of mushrooms that grow in Indonesia and their medicinal benefits. In this systematic review, the author uses PRISMA guideline as the method for evaluating the used articles. The author used PubMed, Science Direct, Wiley, EBSCOHost, Taylor & Francis, and Springer databases with keywords comprising “Mushroom Cultivation in Indonesia”, “Mushroom medicinal benefits”, and “Indonesian mushrooms”. Out of 1190 studies retrieved, 31 articles fit the criteria and can be used as the basis for this review. The author analyzed and extracted the records regarding cultivation mushroom that grow in Indonesia and their medicinal benefits from the studies. The analysis summarized that mushrooms in Indonesia has many medicinal benefits that have been tested with in vivo and in vitro methods.